“Nega maluca”: raça, discursos higienistas e mulheres negras no pós-Abolição (1888-1955) - Silva, Adriana Maria de Souza da (2022)
The objective of this research is to understand how the myth of the "crazy black woman" was configured in the midst of Brazil's modernization period, where the "crazy" become "society waste and a threat to public order". It is known that poor European immigrants, blacks and women considered maladjusted were part of this mass of considered “mentally ill”, who did not fit the profile of the desired population for the young nation that was being born at the end of the 19th century. In the post-abolition period and the formal establishment of “citizenship” for the black population, theories and representations about equality, civilization and nationality emerged and, in the great debates of the time, the affirmation of inferiority and fears about our racial future appear. Behavior, worldviews, religiosity, body control, were part of the concern of the country's political elite, which was based on racist theories developed and defended by most psychiatric doctors, as well as by the psychiatrist and coroner Nina Rodrigues. Starting from the analysis, it is intended to identify the diagnoses addressed to black women and the factors that led to incarceration in Juquery in Franco da Rocha SP, between 1888 and 1955.